(untitled) (Applied Biological Research, 2017)
Meloidogyne incognita is emerging as a major problem in the successful cultivation of gladiolus. The present study was aimed to study the effect of M. incognita on some plant growth parameters of gladiolus cv. ‘Sylvia’ and to demonstrate the histopathological changes in gladioli due to M. incognita infestation. During the experiment, gladiolus crop was found severely infested with M. incognita and showed significant reduction in plant growth parameters and flower production. In severe infestation, no flower was produced. The histopathology of plant roots revealed that 2ndstage juveniles penetrated into root cortex and moved along the cortical layer of cells and started feeding. During feeding process, they produced some hypertrophied cells in vascular cylinder and hyperplasia in pericycle regions. The hypertrophied cells were metabolically highly active, multinucleate and contained dense cytoplasm. In gladiolus, 4-6 such hypertrophied cells were observed in vascular tissues and stellar region of roots. Though the site of infection was vascular tissue but due to the nematode development and giant cell formation, the entire nematode complex and giant cells appeared irregular in root section. The nematodes damaged complete thickness of roots and this condition lead to the destruction of feeder roots which ultimately affected plant growth by reducing water and nutrient absorption from soil.